EXPLORING THE RELATIONSHIP BETWEEN QUALITY OF WORK LIFE AND PERFORMANCE IN HOSPITAL SETTINGS: A BIBLIOMETRIC ANALYSIS - PAMUNGKAS, PROPANA FEMA; AINI , QURRATUL (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background- Quality of Work Life (QWL) is gaining acknowledgment as a key aspect influencing the performance of employees, especially in high-pressure environments like hospitals. However, comprehensive evaluations of its impact in this context remain limited. Objective- This study seeks to fill the research void by analyzing how QWL affects healthcare workers' performance in hospitals through a bibliometric review of recent literature. Method- The study used bibliometric methods to analyze 53 peer-reviewed articles from the Scopus database published between 2015 and 2024. The search employed the keywords "Quality of Work Life" AND "Performance," focusing on English-language publications to ensure consistency. Results- Findings reveal that QWL significantly influences healthcare performance. Key contributing factors include work-life balance, a safe working environment, career development opportunities, and social support. Conversely, poor QWL correlates with burnout, stress, and turnover intention, ultimately reducing productivity and care quality. Conclusion- Improving QWL is a strategic measure to boost optimal performance among the health workforce and enhance the overall quality of hospital services. Hospital leaders must prioritize HRM-based initiatives such as implementing flexible work schedules, improving workplace safety, providing continuous training and development, and cultivating a supportive organizational culture to achieve long-term success and increase job satisfaction among healthcare professionals.